Pengaruh Culturally/Responsive.Teaching,(CRT)’terhadap Motivasi Belajar Siswa pada Materi Sepakbola - Rifqi Andrianto; Nanik Indahwati; Sigra Santika Satria Dhani (CV. Alim's Publishing, 2024)
Education is a conscious and planned effort aimed at developing students' potential to achieve a better life. In the context of physical education, quality learning plays an important role in increasing students' interest and creativity. Physical activity, as taught in PJOK subjects, is very important for students' physical-motor development, especially in junior high school age children. However, observations show that the gross motor development of 7th grade students is not optimal and teachers are less innovative in the use of media and games. Traditional games, such as black and green, can be a solution to improve students' gross motor skills while creating a fun learning atmosphere. This study aims to explore the application of the black and green game in improving the gross motor skills of 13-year-old students, with the hope of making a positive contribution to PJOK learning.